Coronary artery disease is associated with Alzheimer disease neuropathology in APOE4 carriers - Beeri, M S; Rapp, M; Silverman, J M; Schmeidler, J; Grossman, H T; Fallon, J T; Purohit, D P; Perl, D P; Siddiqui, A; Lesser, G; Rosendorff, C; Haroutunian, V (Neurology, 2006)
To examine the associations between postmortem Alzheimer disease (AD) neuropathology and autopsy-verified cardiovascular disease. The authors examined 99 subjects (mean age at death = 87.6; SD = 8.7) from the Mount Sinai School of Medicine Department of Psychiatry Brain Bank who were devoid of cerebrovascular disease-associated lesions or of non-AD-related neuropathology. Density of neuritic plaques (NPs) and neurofibrillary tangles (NFTs) as well as coronary artery and aortic atherosclerosis, left ventricular wall thickness, and heart weight were measured. Partial correlations were used to assess the associations of the four cardiovascular variables with NPs and NFTs in the hippocampus, entorhinal cortex, and multiple regions of the cerebral cortex after controlling for age at death, sex, dementia severity, body mass index, and ApoE genotype. These analyses were also repeated separately for ApoE4 carriers and noncarriers. The extent of coronary artery disease and to a lesser extent atherosclerosis were significantly associated with the density of cardinal neuropathologic lesions of AD in this autopsy sample (significant correlations between 0.22 and 0.29). These associations were more pronounced for the ApoE4 allele carriers (n = 42; significant correlations between 0.34 and 0.47). The degree of coronary artery disease is independently associated with the cardinal neuropathological lesions of Alzheimer disease. These associations are primarily attributable to individuals with the ApoE4 allele.